Safe soundscape in the spa park based on its development plan - Sztubecka, Małgorzata; Mrówczyńska, Maria; Bazan-Krzywoszańska, Anna; Skiba, Marta (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
The areas of human activity are threatened areas occurrence of one of the most nuisance environmental factors - noise. This nuisance refers, in particular, the urban agglomerations. The noise has a negative impact on human health, reduces productivity, makes it difficult to relax and adversely affects the concentration. An indicator of the noise, is a logarithmic measure of sound level - in decibels (dB). Depending on the function and purpose of the area, the law defines the limits of noise levels. They comprise in the range of so-called acoustic comfort. Proper location and design of the green areas has an impact on the comfort of rest. Planning documents, as local law, indicating the purpose of such areas are the basis for their utility program and development. The relevant provisions of development plan allow for a rational form of space. The aim of this article is to pay attention to the problem of noise that occurs outside the interval noticeable comfort and assessment of the possibilities offered by this type of documents in relation to the existing notation (in terms of people sound security staying in these type of areas).